Sonographic Measurement of Brainstem Through the Foramen Magnum in Premature Neonates Can Predict Neurodevelopment Outcome? - Chen, Shyi-Jou; Hu, Chih-Fen; Tien, Chiung-Hsi; Chen, Cheng-Yu (Frontiers in Neurology, 2021)
Background: To investigate whether serial morphometric measurements of the brainstem using high resolution trans-foramen-magnum ultrasound (US) in premature neonates correlate with neurological outcomes. Methods: Serial brain ultrasound scans were performed in 36 consecutive preterm infants born at less than 34 weeks of gestation from birth until term-equivalent age. Two-dimensional brainstem measurements of the pons and medulla oblongata were compared with those in a cohort of 67 healthy full-term newborns. Neurologic assessment of the premature infants was assessed at 5 years of age. Results: Of the 36 preterm infants born between 25 and 34 weeks of gestation, 8 had significantly delayed growth profiles in both the pons and medulla and developed neurological sequelae by 5 years of age. Conclusions: Morphometric measurements of the developing brainstem using high resolution trans-foramen-magnum ultrasound (US) may help predict neurological outcome in high-risk neonates, particularly in those who are born extremely premature.